Resilience of willows (Salix spp.) differs between families during and after flooding according to floodwater depth - Doffo, Guillermo Nestor; Rodríguez, María Emilia; Olguin, Flavia Y.; Cerrillo, Teresa; Luquez, Virginia Martha Cristina (2018)
Although the morphological and physiological responses of willows to flooding have already been characterized, less is known about their responses during the post-flooding period. After the end of the stress episode, plants may modify some leaf and plant traits to compensate for biomass loss. The aim of this work was to analyze the post-flooding responses of different willow genotypes under two different depths of floodwater. The hypothesis was that the growth recovery in the post-flooding period would be different according to the genotype and the floodwater depth. We analyzed three genotypes of five willow families (four interspecific hybrids and one open-pollinated family). The treatments were: (1) Control: plants watered to field capacity; (2) T10: water covering 10 cm above soil level; (3) T65: water covering 65 cm above soil level. Both flooding treatments were followed by a period of recovery (without flooding). Growth was reduced by flooding in T65 but not in T10, while root-to-shoot ratio was reduced in both flooding treatments. The relative growth rate in height, leaf nitrogen concentration, stomatal conductance and electron transport rate changed in a different manner during the post-flooding period, depending on the treatment and genetic background. These results emphasize the need for evaluating a post-flooding recovery period for the breeding of willow genotypes destined for areas under risk of flooding. According to our results, Salix matsudana could be a source of flooding tolerance for willow breeding programs.